De l'évaluation, considérée comme une relation de service - Marc Nagels; Cécile Vourch (Université de Provence, 2009)
The purpose of this study is to formulate an explanatory model of the attitudes of students and teachers confronted with teaching evaluation in higher education. In a service relationship intended to facilitate and regulate learning, this evaluation is seen as having a double dimension of « object of use » by assessing students and of « object of service » by teachers. Three kinds of representations are identified as common to students and teachers. They enlighten the actors' behaviour and the social dynamics which govern evaluation. Situating evaluation within the framework of a service relationship offers a new perspective to training designers: that of compromises, of conversational games and of factors of commitment or of disengagement of teachers in connection with a given institutional context.